Gemcitabine-Induced Extensive Skin Necrosis. (26th November 2012) - D'epiro, Sara; Salvi, Monica; Mattozzi, Carlo; Giancristoforo, Simona; Campoli, Marco; Zanniello, Ramona; Luci, Cecilia; Macaluso, Laura; Giovannoni, Sara; Iacovelli, Roberto; Calvieri, Stefano; Richetta, Antonio Giovanni
Abstract : An 82-year-old woman presented with oedema and extensive necrotic ulcerative lesions on the back side of her lower limbs, emerging after the second cycle of chemotherapy consisting of Gemcitabine for metastatic pancreatic cancer. The absence of any convincing argument in favor of cardiovascular or autoimmune disease led us to attribute the onset of skin necrosis to chemotherapy administration. Although skin ischemia has also been described as a paraneoplastic syndrome, in this case we could observe a temporal and causal relationship to Gemcitabine infusion. Recently, this drug has been associated with important vascular side effects; its vascular toxicity is in fact higher than previously estimated. To our knowledge, careful attention should be reserved to neoplastic patients candidated to Gemcitabine administration, especially if previously affected by arterial vascular disease, venous thromboembolism, or collagenoses.